Production Systems and Agricultural Productivity Factors in the Municipalities of Aileu, Ainaro and Covalima, Timor-Leste - Gomes, Graciano Soares; Code, Carlito de Araújo Mali; Moniz, Augustine da C.; da Silva, Oscar (Seven Editora, 2023)
The purpose of agricultural development is to eradicate hunger and poverty through sustainable production to ensure sustainable consumption in the context of ensuring food self-sufficiency. The study aims to characterize production systems and agricultural productivity factors at the research site. This study was carried out in the municipalities of Aileu, Ainaro, and Covalima and lasted 3 months, from August to October 2021. The descriptive survey method was used, and the intentional sampling method was used to determine the research sites based on the second data of the 2019 Agricultural Census. To determine the sample size, the Slovin method was used and the respondents were obtained using the simple random method. The variables observed, namely the age, experience, and degree of education of respondents, such as production support factors and the main factors of agricultural productivity, include the sales regime of agricultural products. The results revealed that the mean age of the respondents was between 42.12 and 48.06 years, with an experience of 15.65 to 24.18 years as a producer. The degree of education varies between the three municipalities, and the majority of respondents still with literacy occur in the municipality of Covalima. The minimum total agricultural areas are 0.20 ha and the maximum 11 ha with the average of operational areas between 0.75 and 1.98 ha, and abandoned areas between 0.81 and 1.97 ha per respondent. The highest production of rice and corn occurs in the municipality of Covalima, however, the municipality of Aileu and Ainaro showed lower production. About 65 to 85% of producers finance their productive activities on their own and the workforce is about 3 to 6 people per family. The frequency of agricultural productivity varies between the three municipalities, in the municipality of Covalima the production occurs twice of cultivation per year and in the municipalities of Aileu and Ainaro occurs once a year. The most used production systems are conventional systems (without the use of technologies) in the production of rice and corn and extensive systems in livestock. The results also showed that parents have less interest in encouraging young people to continue farming in the future. The regime for the sale of agricultural products varies depending on market access and the buyer arriving at the place of production. DOI: https://doi.org/10.56238/methofocusinterv1-062